2020
DOI: 10.21123/bsj.2020.17.4.1294
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Cloth Simulation on Virtual Human Character Using Enhanced Position Based Dynamic Framework Technique

Abstract: Cloth simulation and animation has been the topic of research since the mid-80's in the field of computer graphics. Enforcing incompressible is very important in real time simulation. Although, there are great achievements in this regard, it still suffers from unnecessary time consumption in certain steps that is common in real time applications.   This research develops a real-time cloth simulator for a virtual human character (VHC) with wearable clothing. This research achieves success in cloth simulation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Cloth simulation is the cradle of position based methods as the pioneer demonstrations are all applied on cloth. Its high‐quality performance on cloth has been well proven in References 30,31. However, it was later found that PBH, 34 integrating with SPH, 32 could also have visual plausibility in fluid simulation while inheriting the advantages of PBD 34–36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloth simulation is the cradle of position based methods as the pioneer demonstrations are all applied on cloth. Its high‐quality performance on cloth has been well proven in References 30,31. However, it was later found that PBH, 34 integrating with SPH, 32 could also have visual plausibility in fluid simulation while inheriting the advantages of PBD 34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…Bender et al introduced another isometric bending constraint for inextensible surfaces in Reference 30, which is suitable for garment simulation. By applying additional positional constraints to represent constant densities in the PBD solver, Ali et al proposed a real‐time cloth simulation method in Reference 31, which generates different wind effects of cloth, tackling the problem of dynamically preserving cloth overlays and wrinkles. Other collision constraints like self‐collisions within cloth, cloth balloons, and strain energy constraints are applied in different scenarios to simulate different cloth conditions.…”
Section: Recent Improvements Of Pbdmentioning
confidence: 99%
“…The demand for the airline industry has increased regardless of age with globalization. Accordingly, the number of tourists has been increasing 1 . However, the limited space of an airplane could be factors of various kinds of stress [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%